Childhood injuries and food stamp benefits: an examination of administrative data in one US state - Colleen M. Heflin; Irma Arteaga; Jean Felix Ndashimye; Matthew P. Rabbitt (BMC, 2020)
Abstract Background Currently in the United States, childhood injuries are the leading cause of mortality and morbidity, resulting in an estimated 9.2 million emergency department visits and $17 billion annually in medical costs. For preschoolers, it is also the leading cause of disability. Methods We use linked administrative data for SNAP and Medicaid in Missouri from January 2010 to December 2013 to explore monthly patterns in the association between SNAP receipt and ER claims due to childhood injury for children age 0-5 and to examine if these patterns are sensitive to the timing of SNAP benefits. We chose the state of Missouri because unlike most states that disburse SNAP benefits within the first 10 days of the calendar month, Missouri pays SNAP benefits between the first twenty-two days of the month, based on the recipient's birthdate and last name. Results SNAP benefits received later in the calendar month are associated with reductions in ER claims for childhood injuries. Furthermore, the final week in the SNAP benefit month is associated with an increase in ER claims for childhood injuries. Conclusion In terms of public policy, our results suggest that having SNAP disbursement later in the month may have benefits for households.